FAKTOR – FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA REMAJA PUTRI DI SMA N 2 KOTA JAMBI - Putri Azzahroh; Foppy Rozalia (Universitas Nasional, 2018)
Anemia is a nutritional problem in the world, especially in developing countries including Indonesia. The number of iron nutritional anemia in Indonesia is 2.3%. Iron deficiency in adolescents results in pallor, weakness, fatigue, dizziness, and decreased concentration of learning. The prevalence rate of anemia in Indonesia is 26,50% for female, 26,9% for fertile woman, 40.1% for pregnant women and 47.0% for infants. Anemia is a medical condition in which the hemoglobin level is less than normal. Hormone levels of Hb in adolescent girls are> 12 gr / dl. Young women are said to be anemic if Hb levels <12 g / dl. This research was analytic descriptive by using cross sectional study design using primary data, and using random sampling that is simple random technique, the sample in this research is female teenager withnumber 88 people in SMAN 2 Jambi City 2017 in june 2017. From research result There was anemia (45,5%), knowledge (28,4%), motivation (61,4%), family support (64,6%), and health officer role (55,7%). From the result of the research, there is correlation between knowledge (p = 0.005), motivation (p = 0,008), family support (p = 0,020), and health officer role (p = 0.001), with anemia incidence among adolescent girls, Less knowledge, less motivation, less family support, and less healthcare professionals, more anemia. It is expected that there will be an increase and the role of health officer to do counseling about the incidence of anemia.